Мультимодальная анальгезия: полипрагмазия в обезболивании или рациональное применение нестероидных противовоспалительных средств для предотвращения хронизации боли - Гладких, Ф.В. (Траєкторія науки = Traektoriâ Nauki = Path of Science. 2020. № 6 (7). С. 4009–4018., 2020)
Pain is the psychophysiological reaction of an entire organism to a damaging factor. According to the literature, 30.0–75.0 % of patients suffer from severe pain in the postoperative period. The greatest risk of chronicity is severe pain after highly traumatic operations and in cases where there is a neuropathic component of acute pain. The purpose of the work is to evaluate the feasibility of using non-steroidal anti-inflammatory drugs with multimodal analgesia to prevent pain chronicity. Despite the detailed mechanisms of pain formation, to date, there is no ideal analgesic or method for the treatment of acute postoperative pain of high intensity. The most significant complication in the use of opioid analgesics is iatrogenic hyperalgesia, which leads to an increase in the intensity of acute postoperative pain, which is also a risk factor for the formation of chronic postoperative pain. It is possible to get closer to solving the problem of adequate postoperative analgesia only by implementing the concept of multimodal analgesia in the clinic, which involves the simultaneous use of two or more analgesics that have different mechanisms of action and have a synergistic effect. The use of the non-steroidal anti-inflammatory drugs as part of multimodal analgesia reduces the risk of their long-term use, due to effective analgesia and prevention of chronic pain syndrome.
Гладких Ф. В. Мультимодальная анальгезия: полипрагмазия в обезболивании или рациональное применение нестероидных противовоспалительных средств для предотвращения хронизации боли. Траєкторія науки = Traektoriâ Nauki = Path of Science. 2020. № 6 (7). С. 4009–4018. DOI: http://dx.doi.org/10.22178/pos.60-5
Keywords: multimodal analgesia; non-steroidal anti-inflammatory drugs; pain; polypharmacy; adjuvant analgesics